Study of Wind Energy Potential for Wind Power Plants Development in the South Coastal Area of Malang Regency - Yahya Darmawan (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
One of the renewable energy sources that has the potential to be developed in Indonesia is wind energy sources, Indonesia has wind energy sources that can be converted to produce up to 60.68 GW of electricity. One of the potential areas to be developed is the southern region of Java Island and wind speed analysis using the wind weilbull approach. wind speed data is taken from Nasa Power satellite data with a wind height of 50 meters with a time span of January 1, 2022 to December 31, 2022. From the calculation of wind speed, it is found that in the coastal area of South Malang the average speed is 4.92 m/s, with the highest speed of 11.18 m/s. From the analysis using the wind weilbull approach, it is found that the South Coast of Malang has a variation in wind speed between 1-12 m / s where the highest speed occurs in the wind speed range of 6 m / s occurs as much as 18.976%, and the occurrence in 1 year occurs for 1547 hours and the electrical energy produced in a year is 413,520,696 watts. By using q-blade simulation with a turbine diameter of 7.8 m, NACA 4412 airfoil type and TSR value of 5.5, the wind turbine capacity is 5.93661 kW with a CP value of 0.4392. Key words: Renewable energy, maximum average wind speed, electrical energy, wind turbine